Bargaining for a better town: a tripartite struggle in Ruwa Town (Zimbabwe), 1986 to 2015 - Muzorewa, Terence T.; Nyandoro, Mark; Nyawo, Vongai Z. (Midlands State University, 2017)
In the Zimbabwean urban set up, residents are represented by politicians in the form of ward councillors when negotiating with the local authorities (Town Councils) for improved services and living conditions in their residential areas. The hegemonic power of councils and councillors in post-colonial urban administration is presented in Zimbabwe historiography as unproblematic. However, although established by law (the Urban Councils Act, Chapter 29:15 of 1987) as custodians of people’s interest in local authorities, the history of Ruwa Town reveals that the councillors’ role in representing the people has been less significant compared to that of the residents’ associations. This questions the relevance of politicians in urban councils. This article examines the major activities of different residents’ associations in Ruwa as they bargained with the Ruwa Local Authorities for a ‘better town’ between 1986 and 2015. It demonstrates that councillors and party politics undermined town development rather than improving the local authority’s town administration. This tripartite relationship created a base for urban protest reflected in the conflicts between residents’ associations and councillors beginning in 1986 when Ruwa was established as a growth point before being upgraded to an urban area. The year 2015 was the climax of the struggle which involved residents, residents associations and town councillors. The overall conclusion of the paper is that councillors and party politics together with shrinking local representation fostered a permanent alliance between residents and residents’ associations against Ruwa Local Authorities and emergent Private Land Developer Companies (PLDCs).